2017
DOI: 10.1016/j.jpubeco.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The value of a healthy home: Lead paint remediation and housing values

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…This study finds a gain-to-funding ratio of 1.4 to 1.7 for the noise mitigation programme. These figures are similar to the corresponding ratios from U.S. lead remediation programmes (Billings and Schnepel 2017;Theising 2019) and smaller than the ratios from Superfund cleanups in the U.S. (Gamper-Rabindran and Timmins 2013), public housing improvements in the Netherlands (Koster and Van Ommeren 2019) and a U.S. urban revitalization programme (Rossi-Hansberg, Sarte, and Owens III 2010).…”
Section: Introductionsupporting
confidence: 50%
“…This study finds a gain-to-funding ratio of 1.4 to 1.7 for the noise mitigation programme. These figures are similar to the corresponding ratios from U.S. lead remediation programmes (Billings and Schnepel 2017;Theising 2019) and smaller than the ratios from Superfund cleanups in the U.S. (Gamper-Rabindran and Timmins 2013), public housing improvements in the Netherlands (Koster and Van Ommeren 2019) and a U.S. urban revitalization programme (Rossi-Hansberg, Sarte, and Owens III 2010).…”
Section: Introductionsupporting
confidence: 50%
“…only state where the mandate increased property values, suggesting that the state's lead-safe certificate model is particularly effective at spurring abatement. Second, Billings & Schnepel (2017) find that federally-funded lead remediations increase home values and have tremendous returns on investments. By showing that unfunded remediation mandates decrease property values and fail to attract families with children into old homes, my findings suggest that liquidity constraints might prevent some landlords from undertaking beneficial investments.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown individuals are willing to pay rent or a price premium to limit or avoid exposure to hazards such as air pollutants or lead (Billings and Schnepel, 2017). The question is whether such patterns are also visible in our sample.…”
Section: Preferences For a Renovated Homementioning
confidence: 82%
“…Similarly, studies on lead paint remediation programs provide evidence of avoidance behavior relative to sources of indoor pollution. Individuals are willing to pay a rent or price premium to be in houses that are certified to be lead-free (Billings and Schnepel, 2017).…”
Section: Housing Conditions and Avoidance Behaviormentioning
confidence: 99%
See 1 more Smart Citation